Climate change and adaptation: The case of Nigerian agriculture - Francesco Bosello; Lorenza Campagnolo; Fabio Eboli (Fondazione Eni Enrico Mattei (FEEM), 2013)
The present research offers an economic assessment of climate change impacts on the four major crop families characterizing Nigerian agriculture, covering more than 80% of agricultural value added. The evaluation is performed shocking land productivity in a computable general equilibrium model tailored to replicate Nigerian economic development until the mid of this century. The detail of land uses in the model has been also increased differentiating land types per agro ecological zones. Uncertainty on future climate is captured, using, as input, yield changes computed by a crop model, covering the whole range of variability produced by an envelope of one RCM and tem GCM runs. Climate change turns to be unambiguously negative for Nigeria in the medium term with production losses, increase in crop prices, higher food dependency on foreign imports and GDP losses in all the simulations after 2025. In a second part of the paper a cost effectiveness analysis of adaptation in Nigeria agriculture is conducted. Adaptation practices considered are a mix of cheaper soft measures and more costly hard irrigation expansion. The main result is that cost effectiveness of the whole package crucially depends on the possibility to implement adaptation exploiting low cost opportunities. In this case all climate change damages can be offset with a benefit cost ration larger than one in all the climate regimes. Expensive irrigation expansion should however be applied on a much more limited acreage compared with soft measures. If adaptation costs are those of the high end estimates, full adaptation ceases to be cost/effective.This points out the need of a careful planning and implementation of adaptation, irrespectively on the type, looking for measures apt to control its unit cost.
Keywords: C68; Q51; Q54; Q15; 330; Climate Change; Impact; Adaptation; Agriculture; CGE Modelling